Novel method for the synthesis of siloxane nanowires and filaments using gold nanoparticle catalysts - Bhagavatula L. V. Prasad; Stoeva, S.; Sorensen, C. M.; Klabunde, Kenneth J.; Zaikovskii, V. (International Conference on Nanoscience and Technology, 2005)
A unique polymerization reaction of alkylsilanes to siloxane nanowires, filaments and tubes in presence of gold nanoparticles and water is presented. The gold nanoparticles, which catalyze this reaction also work as templates restricting the shape of the resulting polymers into wires and tubes. High resolution transmission electron microscopy images clearly reveal the presence of gold nanoparticle at the tip of each wire supporting the template hypothesis. Elemental analyses by different methods confirm the stoichiometry to be C18H37SiO1.5, when the alkylsilane used was C18H37SiH3, thus proving that the alkyl group remains intact during the polymerization reaction.
Keywords: gold nanoparticles; Nanowires; siloxane polymers

Room temperature nitric oxide sensor actualized from Ru-doped SnO2 nanowires - Ramgir, N. S.; Mulla, Imtiaz S.; Vijayamohanan, K. P. (Sensors and Actuators B - Chemical, 2005)
We report synthesis of the novel Ru-doped SnO2 nanowires and their distinctive response towards NO., and liquefied petroleum gas (LPG) in air. These nanowires have been prepared by a simple approach of evaporation of metal oxide at elevated temperature, The sensor exhibits three order of magnitude changes in the conductivity on exposure to NO2 in air at room temperature, Furthermore. Ru being one of the excellent sensitizers towards LPG these wires also exhibits sensitivity at 250&DEG; C. The amount of Ru plays a crucial role in modulating the sensitivity and lowering the operating temperature. © 2005 Elsevier B.V. All rights reserved.
Keywords: LPG; Nanowires; NO2; tin oxide ruthenium oxide

Electron transfer behavior of monolayer protected nanoclusters and nanowires of silver and gold - Sharma, Jadab; Vivek, J. P.; Vijayamohanan, Kunjukrishna P. (Journal of Nanoscience and Nanotechnology, 2006)
Understanding the electron transfer behavior of nanometer sized, both metallic and semiconducting particles and wires is important due to the fundamental interest in size and shape dependent electronic properties and also because of its applications in nano-electronic devices like single electron transistors and molecular switches. Monolayer protected nanoclusters enable one simple and elegant method of synthesis of these types of metallic and semiconducting materials using interfacial chemistry as has been successfully used in several applications ranging from catalysis to molecular electronics. The success of this type of nanostructured materials is due in part to the well known protecting/stabilizing action of the ligands (also known as surface passivating/capping agents), which facilitate the synthesis and processing of these hydrophobic colloids in solution form. The present article discusses the electron transfer behavior of silver nanowires and nanoparticles with varied sizes. In particular, we have investigated the electrochemical properties of silver nanowires (diameter 70 nm, length several micrometers) and compared with the behavior of similar relatively larger sized nanoparticles (size 40 nm). A critical analysis of the redox behavior of silver nanowires and nanoparticles is presented in aqueous medium under various electrolytic conditions along with a comparison of analogous properties of smaller sized (2-7 nm) silver and gold nanoclusters.
Keywords: cyclic voltammetry; nanoclusters/nanoparticles; Nanowires

Influence of process variables on growth of ZnO nanowires by cathodic electrodeposition on zinc substrate - Sheini, Farid Jamali; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A. (Thin Solid Films, 2009)
Influence of the deposition duration and electrolyte concentration on the structural and morphological features of the ZnO thin films, grown by cathodic electrodeposition on zinc substrate followed by annealing in air at 400 degrees C, have been investigated. The surface morphology of the as-synthesized films shows two distinct features, presence of `2-dimensional nanosheets' on the area near the electrolyte-air interface and `granular' nanostructures, below the interface region. However, upon annealing, the formation of ZnO nanowires, possessing length of several microns and diameter less than 20 nm, on the entire substrate is observed. The X-ray and selected area electron diffraction patterns clearly confirm the polycrystalline nature of the ZnO nanowires. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Annealing; Electrodeposition; Nanowires; photoluminescence; scanning electron microscopy; transmission electron microscopy; Zinc oxide

Fabrication of In-doped SnO2 nanowire arrays and its field emission investigations - Bhise, Ashok B.; Late, Dattatray J.; Sathe, B.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Journal of Experimental Nanoscience, 2010)
The field emission of In-doped SnO2 wire array has been performed in parallel plate diode configuration. A maximum current density of 60 mu A/cm2 is drawn from the emitter at an applied field of 4 V/mu m. The nonlinearity in the Fowler-Nordheim plot, characteristics of semiconductor emitter has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability recorded at a preset value of 1 mu A is observed to be good. The high emission current density, good current stability and mechanically robust nature of the wires offer unprecedented advantages as promising cold cathodes for many potential applications based on field emission.
Keywords: cold cathodes; device; Doping; field emission; Nanowires; SnO2

Surface characterization of Au-ZnO nanowire films - Jamali-Sheini, Farid; Yousefi, Ramin; Patil, K. R. (Ceramics International, 2012)
Au-ZnO nanowire films have been synthesized by annealing Zn foils coated with a thin layer of gold. An X-ray diffraction study found that the synthesized ZnO consists mainly of a hexagonal wurtzite structure along with a small amount of AuZn3 phase. Scanning electron images showed that the ZnO wires extend to several microns in length. X-ray photoelectron spectroscopy studies confirmed the oxidation states of Au and Zn. An asymmetric O ls peak indicates the presence of oxygen in an oxide layer and O H groups on the films surfaces. Photoluminescence (PL) spectra showed different visible peaks for pre-annealed films, while for annealed films an UV peak appeared. In addition, the PL analysis showed that the overall intensity of photoluminescence decreased significantly after the films were annealed. Raman spectroscopy results also indicated that the crystalline quality of the films improved with annealing. This could be attributed to a decrease in oxygen vacancies and/or absorption of O-H groups on the surface of ZnO film. The highly hydrophilic surface with a water contact angle of similar to 155 degrees was obtained after annealing in air. (c) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Au-ZnO; Highly hydrophilic; Nanowires; XPS

Synthetic precursor to vertical TiO2 nanowires - Mishra, Biswajit; Ghildiyal, P.; Agarkar, Shruti A.; Khushalani, Deepa (Materials Research Express, 2014)
An easy protocol for improvement in formation of the photoanode in a dye sensitized solar cell is addressed. Specifically, a novel synthesis for the formation of a TiO2 precursor: titanium butanediolate, is detailed. This precursor is found to have higher thermal and temporal stability than commercially available TiO2 precursors and it has successfully been employed in the one-pot synthesis of rutile nanowires grown directly on a conducting substrate: fluorine doped tin oxide (FTO). This synthesis has been further extended to directly form a mixed phase TiO2 film consisting of rutile nanowires along with anatase spherical particles on FTO and this assembly has been used as the photoanode in a dye-sensitized solar cell. The synergistic effect of the two phases has provided a net DSSC efficiency of 4.61% with FF = 61%.
Keywords: Nanomaterials; Nanowires; TiO2

Fuel-influenced nanorod-to-nanosphere transformation of vanadium-doped ZnO and its performance in dye-sensitized solar cells - Kuppusamy, Sasikumar; Mohan, Theanmozhi; Gnana Kumar, G.; Gopinath, Chinnakonda S.; Saha, Arindam; Michael, Robin Jude Vimal (NEW JOURNAL OF CHEMISTRY, 2024)
Keywords: Nanoparticles; Nanowires; Photoanode; Thin-films